Frontal and Insular Input to the Dorsolateral Temporal Pole in Primates: Implications for Auditory Memory - Córcoles-Parada, Marta; Ubero-Martínez, Mar; Morris, Richard G. M.; Insausti, Ricardo; Mishkin, Mortimer; Muñoz-López, Mónica (Frontiers in Neuroscience, 2019)
The temporal pole (TP) has been involved in multiple functions from emotional and social behavior, semantic processing, memory, language in humans and epilepsy surgery, to the fronto-temporal neurodegenerative disorder (semantic) dementia. However, the role of the TP subdivisions is still unclear, in part due to the lack of quantitative data about TP connectivity. This study focuses in the dorsolateral subdivision of the TP: area 38DL in this work. Area 38DL main input originates in the auditory processing areas of the rostral superior temporal gyrus. Among other connections, area 38DL conveys this auditory highly processed information to the entorhinal, rostral perirhinal, and posterior parahippocampal cortices, presumably for storage in long-term memory (Muñoz-López et al., 2015). However, the connections of the TP with cortical areas beyond the temporal cortex suggest that this area is part of a wider network. With the aim to quantitatively determine the topographical, laminar pattern and weighting of the lateral TP afferents from the frontal and insular cortices, we placed a total of 11 tracer injections of the fluorescent retrograde neuronal tracers Fast Blue and Diamidino Yellow at different levels of the lateral TP in rhesus monkeys. The results showed that circa 50% of the total cortical input to area 38DL originates in medial frontal areas 14, 25, 32, and 24 (25%); orbitofrontal areas Pro and PAll (15%); and the agranular, parainsular and disgranular insula (10%). This study sets the anatomical bases to better understand the function of the dorsolateral division of the TP. More specifically, these results suggest that area 38DL forms part of the wider limbic circuit that might contribute, among other functions, with an auditory component to multimodal memory processing.